Evaluation of thyroid function in people vaccinated against COVID-19 via Sinofarm type - Ola Abdul Shaheed Naser, (University of Thi-Qar Journal of Science, 2023)
Background; Since the emergence of the coronavirus disease pandemic, several effective vaccines have been introduced. These vaccines work through several different immunogenic pathways to produce effective immunity. There have been a number of reports of patients developing sub-acute thyroiditis and thyroid dysfunction after receiving the coronavirus (COVID-19) vaccine. This study aims to demonstrate the physiological effect of the covid -19 vaccine on human thyroid hormone. Methodology; For this purpose, 25 samples of male and female blood from people vaccinated with the corona virus used, 25 samples of blood from unvaccinated people were considered as a control group. The effect of this vaccine on the functions of the thyroid gland and on the concentrations of hormones was shown. A significant increase in the concentration of hormone T4 was observed in the group of vaccinated people compared to the control group. Conclusion, the current study Showed that the level of hormones increased significantly in the vaccinated compared to the control group, as well as concluded these results was indicate that thyroid function is negatively affected by the vaccine.